Stock Diseases : Diseases of beef cattle, sheep, goats and farm dogs in temperate Australia - Brightling, A (Sidney: Inkata Press, 1994)
"Stock Diseases" has been written specially for graziers in temperate Australia. The book brings together the information currently available on diseases of beef cattle, sheep, goats and farm dogs in Australia, in a form that is friendly, well illustrated and readily understood. "Stock Diseases" is intended to complement and not replace professional veterinary advice. The book also includes chapters on worm control, vaccination, introduced stock, calving and lambing difficulties, poisonings, exotic diseases, animal welfare and use of veterinary services.
Includes bibliography and index
rpm 17/08/16
Loans
Keywords: Livestock - Diseases; Vetenary hygiene; Stock diseases; Australia